Combining TNF-α silencing with Wnt3a overexpression: a promising gene therapy for particle-induced periprosthetic osteolysis - Chen, Ping; Wu, Long; Zhang, Shuai; Jin, Qunhua; Sun, Kening (Frontiers in Cell and Developmental Biology, 2025)
Wear particle-induced periprosthetic osteolysis is a prevalent issue that frequently leads to the failure of joint replacements, necessitating the development of effective therapeutic strategies. In this study, we established a mouse model of prosthetic loosening and evaluated the therapeutic effects of targeting tumor necrosis factor-alpha (TNF-α) and wingless-type MMTV integration site family, member 3A (Wnt3a) on osteolysis. TNF-α knockdown reduced inflammation and osteoclast-related gene expression, while Wnt3a overexpression increased osteoblast-related gene expression. Notably, the combination of these interventions showed superior efficacy in inhibiting osteolysis compared to monotherapy. Biomechanical imaging and histological staining revealed that combined therapy enhanced bone density and minimized the gaps between the peri-prosthetic bone and the prosthesis, reducing fibrous connective tissue proliferation. Adeno-associated virus-mediated gene therapy was found to be safe, with no adverse effects observed in liver, brain, spleen, and kidney tissues. Our findings suggest that combining TNF-α silencing with Wnt3a overexpression may be a promising approach for treating particle-induced peri-implant osteolysis and warrants further clinical investigation.